Dental student perception and assessment of their clinical knowledge in educating patients about preventive dentistry. (15th July 2014) - Metz, M. J.; Miller, C. J.; Lin, W. S.; Abdel‐Azim, T.; Zandinejad, A.; Crim, G. A.
Abstract In today's dental school curricula, an increasing amount of time is dedicated to technological advances, and preventive dentistry topics may not be adequately addressed. Freshman (D1) students participated in a new Introduction to Preventive Dentistry course, which consisted of didactic lectures, active learning breakout sessions and case‐based studies. The goal of this study was to determine if D1 dental students completing the course had a better knowledge and comfort level with basic preventive dentistry concepts and caries risk assessment than the upcoming graduating senior dental students. Following the completion of the course, D1 students were administered a survey that assessed their comfort level describing preventive dentistry topics to patients. This was immediately followed by an unannounced examination over the same topics. Senior (D4) students, who had not taken a formal course, reported statistically significant higher comfort levels than D1 students. However, the D4s scored significantly lower in all of the examination areas than the D1 students. Higher scores in D1s may have been due to recent exposure to the course material. However, the basic nature of the content‐specific questions should be easily answered by novice practitioners educating their patients on oral disease prevention. As the current data shows lower content‐specific scores of basic preventive dentistry knowledge amongst graduating D4 students, this may indicate a need for more guidance and education of students during the patient care. This study showed that implementation of a formalised course for D1 students can successfully ameliorate deficiencies in knowledge of preventive dentistry topics.